Delivering Digital Data into the Library: The Digimap Project and its Impact on the Map Room– the Bodleian Library Experience - Millea, Nick (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
This paper will consider the Digimap Project – its introduction into the Bodleian Library, how it has evolved, and how digital data’s arrival in the Library might influence future developments.